Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan dengan Disiplin Kerja Sebagai Variabel Intervening Pada PT. Surya Nusantara Sentosa - Aprilita Cintya Maharani; Christina Dewi Wulandari (Journal Research of Social Science, Economics, and Management, 2025)
In the era of global competition, employee performance is a key factor for organizational success, influenced by work environment, motivation, and discipline. PT. Surya Nusantara Sentosa, an automotive service company, faces challenges in maintaining motivation, discipline, and a conducive work environment across its branches. This study analyzes the influence of work environment and motivation on employee performance with discipline as an intervening variable. Data were collected from 240 respondents through questionnaires and analyzed using PLS with SmartPLS 4. The results show that: (1) the work environment does not affect employee performance, (2) work motivation affects employee performance, (3) the work environment affects work discipline, (4) work motivation affects work discipline, (5) work discipline affects employee performance, (6) the work environment does not indirectly affect employee performance with work discipline as an intervening variable, (7) work motivation does not indirectly affect employee performance with work discipline as an intervening variable. These findings emphasize the importance of motivation and work discipline as key factors in improving employee performance, while the role of the work environment is more dominant in shaping discipline than performance directly.